Development of a mismatch amplification mutation assay to correctly serotype isolates of Streptococcus suis serotypes 1, 2, 1/2, and 14 - Lacouture, Sonia (J Vet Diagn Invest, 2020)
Streptococcus suis is one of the most important bacterial swine pathogens worldwide and is an emerging pathogen in humans. There are 29 serotypes, and serotyping, which is based on the antigenicity of the capsular polysaccharide (CPS) or on its coding genes, is often part of routine identification and provides further information regarding S. suis virulence and zoonotic potential. Serotypes 2 and 14 possess high zoonotic potential, and serotype 1/2 is the serotype most frequently isolated from diseased pigs in North America. PCR has replaced antibody-based techniques to perform serotyping. However, traditional PCR is not able to differentiate serotype 2 from 1/2 and serotype 1 from 14, given that the only difference in the cps loci of those serotype pairs is a nonsynonymous single-nucleotide polymorphism. We developed a mismatch amplification mutation assay (MAMA)-PCR that was able to correctly serotype 148 isolates previously known to be serotypes 1, 2, 1/2, or 14. This technique will be highly useful in animal and human health laboratories performing PCR serotyping of S. suis isolates.